The Role of Competitiveness Mechanism Protection of Marketing Performance: Resource-Advantage Theory Perspective - Panjaitan, Roymon (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
The study aims to determine the conceptual and empirical flow of inconsistencies in entrepreneurial, creative relationships on marketing performance centred on protecting competitiveness mechanisms. This conception is built to explore the critical role of protecting the competitiveness mechanisms of entrepreneurial creativity and product innovativeness. Optimization of post-pandemic marketing performance requires creativity and innovativeness and the importance of safeguarding competitiveness mechanisms. Seven hypotheses were developed and tested with the SEM-PLS technique in a sample frame of 230 MSMEs in Central Java, Indonesia. The study's findings contribute to the protection of competitiveness mechanisms conceptually, both empirically and practically. First, directly entrepreneurial creativity has a positive impact. On the contrary, there is a negative relationship of products innovatively in marketing performance. Second, the protection of competitiveness mechanisms can positively bridge innovative product relationships and entrepreneurial creativity in marketing performance. Third, the potential mediator of protection of competitiveness mechanisms can overcome the negative association of product innovativeness on marketing performance. The practical implications of criticizing MSMEs are not enough just creative and innovative, but still, require the protection of resource excellence. External factors protecting intellectual competitiveness mechanisms contribute to providing a competitive advantage. The theoretical implication is that the theory of competing resource advantages that a competitor's scarce resources have has the potential to gain a comparative advantage.